# Difference between revisions of "Integration by parts for delta integrals with no sigma in integrand"

From timescalewiki

Line 1: | Line 1: | ||

+ | __NOTOC__ | ||

==Theorem== | ==Theorem== | ||

The following formula holds: | The following formula holds: |

## Latest revision as of 14:48, 13 March 2018

## Theorem

The following formula holds: $$\int_a^b f(t) g^{\Delta}(t) \Delta t = (fg)(b) - (fg)(a) - \int_a^b f^{\Delta}(t) g(\sigma(t)) \Delta t,$$ where $\int$ denotes the delta integral.

## Proof

## See also

Integration by parts for delta integrals with sigma in integrand